Pharmaco‐electroencephalographic responses in the rat differ between active and inactive locomotor states. (1st April 2019) - Hansen, Ingeborg H.; Agerskov, Claus; Arvastson, Lars; Bastlund, Jesper F.; Sørensen, Helge B. D.; Herrik, Kjartan F.
Abstract: Quantitative electroencephalography from freely moving rats is commonly used as a translational tool for predicting drug‐effects in humans. We hypothesized that drug‐effects may be expressed differently depending on whether the rat is in active locomotion or sitting still during recording sessions, and proposed automatic state‐detection as a viable tool for estimating drug‐effects free of hypo‐/hyperlocomotion‐induced effects. We aimed at developing a fully automatic and validated method for detecting two behavioural states: active and inactive, in one‐second intervals and to use the method for evaluating ketamine, DOI, d‐cycloserine, d‐amphetamine, and diazepam effects specifically within each state. The developed state‐detector attained high precision with more than 90% of the detected time correctly classified, and multiple differences between the two detected states were discovered. Ketamine‐induced delta activity was found specifically related to locomotion. Ketamine and DOI suppressed theta and beta oscillations exclusively during inactivity. Characteristic gamma and high‐frequency oscillations (HFO) enhancements of the NMDAR and 5HT2A modulators, speculated associated with locomotion, were profound and often largest during the inactive state. State‐specific analyses, theoretically eliminating biases from altered occurrence of locomotion, revealed only few effects of d‐amphetamine and diazepam. Overall, drug‐effects were most abundant in the inactive state. In conclusion, this new validated and automatic locomotion state‐detection method enables fast and reliable state‐specific analysis facilitating discovery of state‐dependent drug‐effects and control for altered occurrence of locomotion. This may ultimately lead to better cross‐species translation of electrophysiological effects of pharmacological modulations. Abstract : An automatic method for estimating drug effects on neuronal oscillatory activity in two behavioural states: active and inactive, was developed. Testing the method on ketamine, d‐cycloserine, DOI, amphetamine, and diazepam, we found that drug‐effects depended on whether the rat was in active locomotion or sitting still during recording sessions. Fast and reliable state‐specific analyses may greatly improve the translational value of rodent pharmaco‐encephalography towards human EEG studies.